2013
DOI: 10.4097/kjae.2013.65.1.42
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the onset time of complete blockade of the sciatic nerve in the application of ropivacaine and its equal volumes mixture with lidocaine: a double-blind randomized study

Abstract: BackgroundThe purpose of the current study is to create a new mixture of local anesthetics-one with a short time of block development and short action term (5 ml of 1% lidocaine solution) and another with a longer time of anesthesia development and a long analgetic effect (5 ml of 0.75% ropivacaine)-for use during surgical operations on extremities. The primary end point was the development of the complete sensory block of the sciatic nerve.MethodsSixty blocks of sciatic nerve were used in a double-blind rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…It is also suggested that the time of development of anesthesia for the same amount of local anesthetic should lengthen when the distal blockade is being performed because connective tissue is the main obstacle to the diffusion of anesthetic to axons [4]. Indirectly, the hypothesis by N. Moayeri et al about the amount of connective tissue as the principal obstacle to the diffusion of local anesthetic blocking the sciatic nerve was previously confirmed in our study where we proved that while performing the posterior blockade of the sciatic nerve under ultrasound guidance the reduction of the amount of 0.75% ropivacaine solution from 10 ml to 5 ml significantly increases the time of the development of complete sensory and motor blocks [19]. Our data acquired for lidocaine confirm the results obtained by M. Taboada et al for ropivacaine and mepivacaine which indicated the increase of the time of the popliteal sciatic nerve blockade [6] [7].…”
Section: Discussionsupporting
confidence: 75%
“…It is also suggested that the time of development of anesthesia for the same amount of local anesthetic should lengthen when the distal blockade is being performed because connective tissue is the main obstacle to the diffusion of anesthetic to axons [4]. Indirectly, the hypothesis by N. Moayeri et al about the amount of connective tissue as the principal obstacle to the diffusion of local anesthetic blocking the sciatic nerve was previously confirmed in our study where we proved that while performing the posterior blockade of the sciatic nerve under ultrasound guidance the reduction of the amount of 0.75% ropivacaine solution from 10 ml to 5 ml significantly increases the time of the development of complete sensory and motor blocks [19]. Our data acquired for lidocaine confirm the results obtained by M. Taboada et al for ropivacaine and mepivacaine which indicated the increase of the time of the popliteal sciatic nerve blockade [6] [7].…”
Section: Discussionsupporting
confidence: 75%
“…Group R received a single injection of the RLB with 30 mL of local anesthetic mixture (0.75% ropivacaine 20 mL + 2% lidocaine 10 mL) and IV-PCA. We planned to use a mixture of ropivacaine and lidocaine to reduce the onset time of the RLB without reducing postoperative analgesia duration [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the authors designed the use of a 20-ml mixture of rapid-acting agent with short duration of effect (10-ml of 2% lidocaine with epinephrine 1:200,000), and long-acting agent with long duration of effect (10-ml of 0.5% levobupivacaine) - which was different from the previous studies 14 - 16 . This - combined local anaesthetics (LA) solution would result in an early aneesthetic effect (approximately 20 minutes) which allow the anaesthesiologists to perform two blocks without delay without the need to use a high dose of levobupivacaine 25 , and also have a similar duration of analgesic benefit extended beyond six hours - comparable to the other studies 14 - 16 . Moreover, we also found that 20 mL of LA is sufficient for effective lumbar plexus block without serious complications like bilateral anesthesia (from unintentionally bilateral intrathecal/epidural drug spreading) or vascular administration of LA that had seen in traditional lumbar plexus block with large LA volumes (30-40 mL) 26 .…”
Section: Discussionmentioning
confidence: 91%